(untitled) - Stevenson, Harold W. (New York, 1992)
This book introduce about compares United States elementary education practices with those in Asia and comes to some surprising conclusions.
Keywords: Giáo dục, Tiểu học,Education, Elementary; Hoa Kỳ,United States